Inovasi Digital pada Pemerintah Kabupaten Sumedang dalam Mendorong Open Government - Barsei, Adhityo Nugraha; Nugroho, Setiyatmo Adi; Ghassani, Ghina Aghnia; Trianita, Linda Novi (Research and Development Agency Ministry of Home Affairs, 2023)
Sumedang Regency is one of the Regional Governments that has a high commitment in innovating digital services. However, digital service innovations carried out by the Sumedang Regency Government have never been reviewed from an open government perspective. This research aims to explain superior digital innovations and how far these innovations have encouraged the realization of open government. This research uses a case study approach through interviews and documentation studies. Then the data is analyzed by simplifying the data, compiling the data, and drawing conclusions. The research results show Sumedang Regency is not only capable of innovating digital. Through superior digital services, Sumedang Regency has been able to realize transparency in information and regional performance, participation in public services, and collaboration in handling stunting. These findings can be a reference for other regional governments who want to realize open government through digital innovation.